Role of Nuclear Medicine in Evaluation of Pediatric Kidney Disease: Obstructive Uropathy - R. L. Vijayaraghavan (Indian Journal of Kidney Diseases)
Diuretic renography is commonly used for evaluation of congenital pelviureteric junction obstruction. Knowledge of renal maturity and pathophysiology of obstructive uropathy helps in selection of proper radiopharmaceutical, diuretic protocol and generating meaningful reports from renography. Various physical, physiological, and technical factors affect the procedure and interpretation of renography. Standardization of procedure and protocols is essential and can be accessed from joint consensus procedure guidelines published in 2018 by European Association of Nuclear Medicine (EANM) and The Society of Nuclear Medicine and Molecular Imaging (SNMMI). Renal maturity, pathophysiology of pelviureteric obstruction, choice of radiopharmaceuticals, protocol, interpretation, and pitfalls of diuretic renography are discussed in this article.